Legal Position of Eigendom Verponding Land Rights in the Indonesian Land System - Edwiarka, Salvataro Djibran (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to determine the legal position of eigendom verponding land rights in the land system in Indonesia and to determine the mechanism for the transfer of eigendom verponding land rights to land ownership rights in the land system in Indonesia. The approach method used in this qualitative legal research is the sociological juridical approach method, which is an approach by seeking information through direct interviews with informants empirically first and then continued by conducting secondary data research found in literature studies through theoretical steps. Based on the results of the research conducted, it was found that the ownership of former eigendom verponding land in Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA) and its implementing regulations, as well as Government Regulation Number 24 of 1997 concerning land registration states that the land is land controlled by the state with the legal status of state land, where former eigendom verponding is included in state land that is not free or cannot be owned by individuals and the eigendom verponding certificate is not valid proof of ownership. Then, as a result of the law on former eigendom verponding land that has not been converted, for the rights holder, the proof of ownership of the former eigendom verponding is considered invalid. Rights holders can still register land through applications and granting of land rights with the obligation of physical control. Applications submitted for land with state land status are no longer eigendom verponding. Physical control of land as a real relationship between the rights holder as the subject of land rights with his land in order to be able to register his land. Holders of former eigendom verponding rights who still fulfill the requirements as subjects of land rights can actively utilize their land.